Assessing the Effectiveness of Children Safe Spaces (Children's Corners) on the Lives of Orphans and Vulnerable Children: A Case of Chanyungu Children's Corner in Machinga District - Matiti, Lawrence; Velmurugan, Dr.T. (International Journal of Scientific Research and Management (IJSRM), 2022)
The HIV and AIDS epidemic is exerting the pressure on the immediate and extended family that the traditional care and support system has been stretched to the limit. Despite this, the family and the community are still the best providers of care and support to children. In response to the negative effects that children are facing, Government of Malawi introduced childrens corners as a community-based structure that, if properly implemented, can offer community parenting to address some of the childrens challenges.  In exploring the effectiveness of these child safe spaces (childrens corners) on the psychosocial lives of orphans and vulnerable children, this study will be carried out in Chanyungu Village in Machinga District - Malawi. The researcher has an assumption of that childrens corners help to bring change in the lives of children such that if the programs are more targeted on the vulnerable children they can help to reverse the impact of vulnerability.This research will try to establish that vulnerable children acquire adequate information from childrens corners and it is this information that will help them change behaviour because they interact with their peers and share experiences. Previous studies done in other countries has also found that effective interventions such as peer education, resilience building are needed to help the vulnerable children maintain coping skills on challenges of life.